Measuring the Impact of Livestock Development and Red Meat Production on Water Consumption in the Agricultural Sector in the Kingdom of Saudi Arabia (International Journal of Financial, Administrative and Economic Sciences, 2025)
Given the increasing livestock population and red meat production amidst water scarcity, this study aimed to measure the impact of livestock development on water consumption in the agricultural sector using economic equations and econometric analysis. The study revealed that livestock numbers increased to 30.71 million head in 2023, and red meat production grew at an annual growth rate of 2.9%. The amount of water required for livestock and red meat production increased from 1.53 billion m³, representing 8.52% of total water consumption in the agricultural sector in 2000, to 2.86 billion m³, representing 23.23% of total water consumption in the agricultural sector in 2023. The total water required for livestock and red meat production is expected to increase from 2.77 billion m³ in 2024 to 3.32 billion m³ in 2030. Water consumption in the agricultural sector is also expected to increase from 12.39 billion m³ in 2024 to 15.95 billion m³ in 2030, thus impacting strategic water reserves and decreasing groundwater levels, especially in sedimentary aquifers. Finally, this study recommends regulating livestock numbers to ensure continued water conservation and sustainability for future generations.
Keywords: Livestock; Red Meat; Water Consumption; Agricultural Sector